Role of Knowledge Management in Ensuring Quality of Higher Education in Al-Quds University from the Academic Staff's Perspective - Bushra Izzat Albadawi; Mohammad Omran Salha (University of Science and Technology, Yemen, 2021)
The concept of knowledge management has acquired significance recently for its relevance to the concept of total information management. This study aimed to investigate the role of knowledge management in ensuring quality of higher education in Al-Quds University from the viewpoint of academics. To achieve this objective, the descriptive, analytical method was followed. (150) academics were randomly selected for the study from Al-Quds University during 2019/2020. A questionnaire was developed based on previous studies; and after checking its reliability and validity, it was used to collect data. The data was analyzed by using SPSS to conduct statistical procedures, including T-test and ANOVA. Major findings revealed that there was a positive role for Operations management knowledge in quality assurance, and the academics' assessment regarding knowledge management and quality assurance practice was medium. The independent variables (knowledge creation, knowledge sharing, application and generation of knowledge) combined had a positive effect on the dependent variable (achieving quality of higher education at Al-Quds University). It was also found that there was a positive effect for the knowledge sharing variable. In other words, the higher the level of knowledge management is, the greater the achievement of the quality of higher education at Al-Quds University is. The independent variables (gender, academic rank, college) had an impact on the dependent variable (achieving the quality of higher education at Al-Quds University). It was found that there was a positive effect for the academic rank variable, and a negative effect for the college variable, which means that the higher the academic rank is, moving towards science colleges, the more the quality of higher education at Al-Quds University will be, which means knowledge management helps in achieving the quality of higher education. The study recommended the need to raise the efficiency of knowledge management processes at Al-Quds University because of its role in achieving higher education quality. keywords: management knowledge, quality of higher education, Al-Quds university.